Ceftazidime-avibactam for the Treatment of Multidrug-resistant Pseudomonas aeruginosa Central Nervous System Infection in Pediatric Patient: A Case Report. Issue 5 (21st December 2021) - Almangour, Thamer A.; Alsubaie, Sarah; Ghonem, Leen; Almohaini, Hissah A.; Mohammed Bakheet, Hind; Altweijri, Ikhlass
Abstract : Very limited experimental and clinical data are currently available regarding the cerebrospinal fluid (CSF) penetration of ceftazidime-avibactam in adults. Nevertheless, up to our knowledge, there are no data of ceftazidime-avibactam use in central nervous system infections in pediatric patients. For that, here we describe our experience with the use of ceftazidime-avibactam in addition to intraventricular colistin in a pediatric patient diagnosed with ventriculoperitoneal shunt infection due to multidrug-resistant P. aeruginosa . A 2-year-old boy known to pre-term, delivered at 26 weeks with hydrocephalus that required ventriculoperitoneal shunt which was infected due to P. aeruginosa. He was treated with multiple antipseudomonal agents; however, cultures remained persistently positive. On day 54 of admission, the isolate was reported as multidrug-resistant P. aeruginosa and he was switched to ceftazidime-avibactam and intraventricular colistin. CSF cultures became sterile 3 days after initiation of this antibiotic regimen, and subsequent CSF cultures had no growth. No recurrent episode of central nervous system infections due to P. aeruginosa occurred up to 2 years of follow-up.